Photo-response of silver-TiO2 film - Viernes, Meryll Angelica J. (Animo Repository, 2014)
Silver and TiO2 films were deposited on glass substrates via the plasma sputter type negative ion source and a compact planar magnetron, respectively. A silver target was biased and is sputtered by argon plasma for 30 min. TiO2 was deposited by sputtering a titanium disk and introducing oxygen in a 1:13 ratio with argon plasma for 2 h. The resulting composite films (silver on TiO2 and TiO2 on silver) were analyzed by its transmissivity in the UV-VIS region showing increased optical absorbance. The synthesized films were used in the photocatalytic degradation of methylene blue showing an increase in photocatalytic degradation when only TiO2 is used. The introduction of silver with TiO2 inhibited the effective photocatalytic degradation of methylene blue.